ACQUIRING LEGITIMACY: THE IMPACT OF CIS INTERPARLIAMENTARY INSTITUTIONS ON POST-SOVIET PARLIAMENTARIANISM - MURZAKULOVA, Asel (CENTRAL ASIA AND THE CAUCASUS, 2014)
This article analyzes the institutional specifics of CIS interparliamentary institutions in the context of regime transformation. It examines the collective benefits from Kyrgyzstan’s cooperation with the Interparliamentary Assembly of CIS Member States (IA CIS). According to the author, the IA CIS directs its efforts toward upholding the standards of adaptive parliamentarianism in its member states. It initially aimed to coordinate a unified election assessment among its member states, whereby it has managed to create the impression that it is a structure subordinated to the legitimization of authoritative regimes.